Russia since 1980 wrestling with westernization - Rosefielde, Steven 1942-; Hedlund, Stefan 1953- (The World since 1980, 2009)
Russia Since 1980 recounts the epochal political, economic, and social changes that destroyed the Soviet Union, ushering in a perplexing new order. Two decades after Mikhail Gorbachev initiated regime-wrecking radical reforms, Russia has reemerged as a superpower. It has survived a hyperdepression, modernized, restored private property and business, adopted a liberal democratic persona, and asserted claims to global leadership. Many in the West perceive these developments as proof of a better globalized tomorrow, while others foresee a new cold war. Globalizers contend that Russia is speedily democratizing, marketizing, and humanizing, creating a regime based on the rule of law and respect for civil rights. Opponents counterclaim that Russia before and during the Soviet period was similarly misportrayed and insist that Medvedev's Russia is just another variation of an authoritarian 'Muscovite' model that has prevailed for over five centuries. The cases for both positions are explored while chronicling events since 1980